Tetraspanin co029 expression as a tumor biomarker for monoclonal antibodies preparation: antigenic assessment in colorectal cancer cells - Lucelia Coutinho; Camila Corsini; Jessica Assis; Maria Luysa Pedrosa; Wander Jeremias; Viviane Santos; Monica Cabral; Ana Sofia Mesquita; Matheus Viviani; Angelica Nogueira-Rodrigues; Rafaella Grenfell (Brazilian Journal of Oncology, 2022)
Introduction: The identification of innovative cancer biomarkers is a very relevant ongoing quest. Moreover, their role in cancer diagnosis and clinical management has been radically changed in the last few years with the major emphasis on cancer molecular classification, therapeutic target identification, and therapeutic protocol responsivity. tetraspanins are a family of transmembrane proteins correlated with tumor stage, tumor type and patient outcome affecting cell growth, morphology, invasion, and metastasis.